GROWTH MINDSET, HARDINESS DAN SUBJECTIVE WELL-BEING PADA SISWA SEKOLAH MENENGAH ATAS - Sas, Shania Finnalia; Wahidah, Fatin Rohamah Nur (Jurnal Psikologi, 2024)
Often found schools with some students who have lower middle economic status. With these conditions, adolescent students who are in the transition period from childhood to adulthood are expected to have a high level of subjective well-being because this is related to the ability to regulate emotions and overcome problems, in addition, students must be able to think positively and be resilient in facing the economic conditions of their parents. The existence of a growth mindset and hardiness can make students evaluate their lives positively. This study aims to test the effect of growth mindset and hardiness on subjective well-being in high school students. This study uses a quantitative method with a simple random sampling technique. The subjects of this study were 184 high school students. Data were collected by modifying the growth mindset scale instrument, the hardiness personality scale, and the subjective well-being scale. The analysis technique used is the multiple regression technique. The results of this study indicate that hardiness has a more significant effect on subjective well-being with an R2 contribution of 0.161%. In addition, growth mindset also influences subjective well-being with an R2 contribution of 0.022% and if combined, growth mindset and hardiness mutually strengthen the subjective well-being of high school students, namely the contribution obtained by R2 of 0.162%. The researcher's findings show that growth mindset and hardiness have a significant influence on subjective well-being in high school students.